2012
DOI: 10.3171/2012.2.jns111881
|View full text |Cite
|
Sign up to set email alerts
|

The effect of increased mobility on morbidity in the neurointensive care unit

Abstract: ObjectThe detrimental effects of immobility on intensive care unit (ICU) patients are well established. Limited studies involving medical ICUs have demonstrated the safety and benefit of mobility protocols. Currently no study has investigated the role of increased mobility in the neurointensive care unit population. This study was a single-institution prospective intervention trial to investigate the effectiveness of increased mobility among neurointensive care unit p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
81
2
15

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(101 citation statements)
references
References 30 publications
3
81
2
15
Order By: Relevance
“…A recent study by Titsworth et al suggests that comprehensive UTI prevention efforts along with continuous quality improvement programs can significantly reduce the duration of urinary catheterization and the rate of catheterassociated UTIs in a neurological ICU. 47 Age and baseline comorbidities were clear risk factors for HACs in our patient cohort. Individuals > 80 years of age were significantly more susceptible than younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Titsworth et al suggests that comprehensive UTI prevention efforts along with continuous quality improvement programs can significantly reduce the duration of urinary catheterization and the rate of catheterassociated UTIs in a neurological ICU. 47 Age and baseline comorbidities were clear risk factors for HACs in our patient cohort. Individuals > 80 years of age were significantly more susceptible than younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen prospective studies have been conducted in adults [3,[28][29][30][31][32][33][34][35][36][37][38][39], but only 3 are randomized controlled trials [30,34,39]. A recent Canadian survey, composed of 198 adult ICUs, indicated that although 71% of the units prioritized early mobilization, only 38% of the ICUs had mobilization protocols.…”
Section: Early Mobilization In Critically Ill Patientsmentioning
confidence: 99%
“…Even in neurointensive care patients, increasing mobility has been found to result not only in a reduced length of stay in the ICU, but also in a reduction in the number of infections [5]. These beneficial effects are due not only to less sedation being used in most ICUs in the Western world in accordance with protocols addressing the level of sedation, but also to the use of short-acting sedatives, such as dexmedetomidine [6].…”
mentioning
confidence: 99%